Pavers of the way: Enablers to a lived calling in an Australian context - Duperouzel, Christian (Springer Nature, 2021)
The aim of this paper is to identify and explore ‘enablers’ to a lived calling: those people, things or events that pave the way for individuals to live their calling. These enablers emerged from a study of sixty-five Australian respondents across a range of industries. The results of the research, which utilised the grounded theory research methodology and collected data using semi-structured interviews, showed that the most prominent enablers to a lived calling were: (1) embracing opportunities and making the most of them; (2) support from others; (3) self-confidence/belief; (4) education and financial resources; (5) luck and (6) experience.